Development of Chlorella vulgaris as an alternative protein and mineral source for pandesal fortification - Obis, Albert R. Jr (College of Home Economics, University of the Philippines Diliman, 2023)
Chlorella vulgaris are microalga that have several nutritive properties such as protein, vitamins, minerals, and other essential nutrients. Due to their properties, food manufacturers utilized the algae for food fortification. However, despite the increasing trend of using Chlorella vulgaris as a supplement and food fortifier globally, the use of microalgae in food in the Philippines has yet to be conducted. The study utilized Chlorella vulgaris as a potential protein and mineral source for food fortification in pandesal. Here, C. vulgaris was incorporated in the production of pandesal as a partial flour substitute with three different sample concentrations, 2%, 3%, and 5%. Upon proximate analysis of protein and mineral among the samples, the partial substitution of C. vulgaris flour showed an increase in both protein and mineral concentrations, with 3% of samples having the highest content for protein and minerals. The test for consumer acceptability of C. vulgaris pandesal showed an overall mean of 6.65 ± 1.55, with 3% concentration having the highest overall mean acceptability of 6.81 ± 1.33 followed by 2% and 5% with a score of 6.62 ± 1.60 and 6.54 ± 1.71 respectively. Moreover, all five sensory ratings were significantly and positively correlated with the overall acceptability of all concentrations, with Taste and Texture having the highest correlation to overall acceptability. However, C. vulgaris in pandesal had no significant difference between overall acceptability and concentrations, which can be attributed to masking the concentrations of samples. On the other hand, sex had a significant difference in overall acceptability, which further supports the descriptive data of men evaluating the samples higher than women. Further development of microalgae such as Chlorella vulgaris in local food products would provide a wider option for food fortification as well as address nutrient deficiencies among Filipinos.